An unusual presentation of Rubinstein-Taybi Syndrome with bilateral postaxial polydactyly - Pallavi Sachdeva; Priyanka Minocha; Anita Choudhary; Sadasivan Sitaraman; Manisha Goyal (Hygeia Press di Corridori Marinella, 2016)
Rubinstein-Taybi Syndrome (RSTS) is a rare multiple congenital anomaly syndrome. Only 250 cases have been described in medical literature. We hereby present a 10-month-old male child with characteristic facial features and hand and feet anomalies. The characteristic features of hands and feet typically described are broad thumbs and halluces and clinodactyly of the 5th finger, whereas polydactyly is a rarely reported feature in this syndrome. This case promotes awareness regarding this syndrome and emphasises rarely reported features that should raise high degree of suspicion in a child presenting with multiple congenital anomalies and have a great importance in diagnosis of a genetic syndrome like RSTS. Early detection is essential for prevention of morbidity, mortality and disability.